Deregulation of Adaptive T Cell Immunity in Multiple Myeloma: Insights Into Mechanisms and Therapeutic Opportunities - Leblay, Noémie; Maity, Ranjan; Hasan, Fajer; Neri, Paola (Frontiers in Oncology, 2020)
Immunotherapy has recently emerged as a promising treatment option for multiple myeloma (MM) patients. Profound immune dysfunction and evasion of immune surveillance are known to characterize MM evolution and disease progression. Along with genomic changes observed in malignant plasma cells, the bone marrow (BM) milieu creates a protective environment sustained by the complex interaction of BM stromal cells (BMSCs) and malignant cells that using bidirectional connections and cytokines released stimulate disease progression, drug resistance and enable immune escape. Local immune suppression and T-cell exhaustion are important mediating factors of clinical outcomes and responses to immune-based approaches. Thus, further characterization of the defects present in the immune system of MM patients is essential to develop novel therapies and to repurpose the existing ones. This review seeks to provide insights into the mechanisms that promote tumor escape, cause inadequate T-cell stimulation and impaired cytotoxicity in MM. Furthermore, it highlights current immunotherapies being used to restore adaptive T-cell immune responses in MM and describes strategies created to escape these multiple immune evasion mechanisms.